2008
DOI: 10.1021/jp806159b
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Heterogeneity in Glassy o-Terphenyl. 2. Measurement of Environment Structure Lifetime Using Reversible Reactions

Abstract: A new method is proposed for measuring the lifetime of heterogeneities in a glassy matrix. UV-vis absorption spectroscopy has been used to monitor the kinetics of photoinduced cis-->trans isomerization of 1-naphthyl-azomethoxybenzene (NAMB) in o-terphenyl (OTP) below T(g). The dependence of isomerization rate on the duration of dark interval after generation of cis molecules was established; an increase in the dark interval causes a decrease in isomerization rate. This dependence is shown to be due to the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
(141 reference statements)
0
5
0
Order By: Relevance
“…In this case, Q was observed to decrease strongly with temperature such that no contradiction with the NMR results appeared [155]. In a more recent study, the long exchange times for o-terphenyl at T g could not be confirmed, as measurements using photochromic probes were indicative of Q ≈ 2 [190]. Solvation dynamics experiments covering the time window of 50 s-3 ms regarding τ α resulted in Q > 9 [191], but the timescale of collective solvent responses as detected by the Stokes shift correlation function turns out a factor of 6 faster than other common metrics of structural relaxation.…”
Section: Heterogeneitymentioning
confidence: 77%
“…In this case, Q was observed to decrease strongly with temperature such that no contradiction with the NMR results appeared [155]. In a more recent study, the long exchange times for o-terphenyl at T g could not be confirmed, as measurements using photochromic probes were indicative of Q ≈ 2 [190]. Solvation dynamics experiments covering the time window of 50 s-3 ms regarding τ α resulted in Q > 9 [191], but the timescale of collective solvent responses as detected by the Stokes shift correlation function turns out a factor of 6 faster than other common metrics of structural relaxation.…”
Section: Heterogeneitymentioning
confidence: 77%
“…The simulation procedure is described in more detail elsewhere. 41 Numerical simulations of the isomerization kinetics using the model of random changes fail to provide adequate description of the experimental curves (the simulation results are not presented). The reason for the failure can be understood from the qualitative analysis of the kinetic curves shown in the bottom panel of Figure 4: the slowest molecules do not manifest themselves in the kinetics of isomerization at low τ dark values (5À15 min).…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…The equilibrium values of C i ( t ) and k i were found from the kinetic curves obtained at the maximum value of τ dark . The simulation procedure is described in more detail elsewhere …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations